Preoperative clinical symptomatology and stroke burden in pediatric moyamoya angiopathy: Defining associated risk variables. (November 2021) - Hackenberg, Annette; Battilana, Bianca; Hebeisen, Monika; Steinfeld, Robert; Khan, Nadia
Abstract: Objective: To evaluate the preoperative clinical and magnetic resonance imaging and angiography (MRI-MRA) characteristics in pediatric moyamoya patients. Methods: Analysis included 100 children with moyamoya angiopathy referred to our moyamoya center for preoperative evaluation. Clinical symptoms, neurological status using Pediatric Stroke Outcome Measurement (PSOM) and degree of disability on modified Rankin scale score (mRS) were evaluated. MRI-MRA evaluation included the assessment of ischemic lesions and involvement of posterior circulation. Data were analyzed for moyamoya disease (MMD), moyamoya syndrome (MMS) and age at disease onset. Results: Stroke was a common presentation in both MMD and MMS patients. TIAs and headaches/migraine were more frequent in MMD. There was no evidence of a difference in stroke burden on MRI as well as in PCA involvement between the two subgroups. Children <2 years had higher odds of having a stroke (OR 15.5, 95% CI 3.8–62.4, p < 0.001), recurrent stroke (OR 11.8, 95%CI 2.9–46.7, p < 0.001) and unfavorable mRS (≥2) (OR 4.2, 95% CI 1.3–13.7, p = 0.01) when compared to those >5 years of age. There was some evidence of association of PCA involvement with recurrent strokes (OR 3.1, CI 1.0–9.6, p = 0.05), a poor PSOM (OR 3.0, 95% CI 1.1–8.2, p = 0.04) and mRS (OR 3.1, 95% CI 1.2–8.3, p = 0.02). Conclusion: Stroke seems to be a common presentation in both MMD and MMS patients. Early age at symptom onset and involvement of posterior circulation seem to be important risk factors for a high stroke burden and an unfavorable PSOM and mRS. Highlights: Age at first presentation i.e. symptom onset is an important risk parameter for unfavorable disease course. Children < 2 years present with a high risk of recurrent cortical strokes, associated with functional deficit and epilepsy. Children > 5 years frequently present with TIAs and headaches and atypical symptoms like drop attacks and limb shaking. Posterior circulation involvement seems to be associated with a higher risk of stroke and unfavorable clinical presentation.